Body Position and Ventilator-Associated Pneumonia Prevention - Bassi, Gianluigi Li; Xiol, Eli Aguilera; Pagliara, Francesco; Hua, Yang; Torres, Antoni (Seminars in Respiratory and Critical Care Medicine, 2017)
Seminal studies have demonstrated that tracheally intubated, mechanically ventilated patients, positioned in supine horizontal position, are at a high risk of developing ventilator-associated pneumonia, through aspiration of gastric pathogens. In the 1990s, innovative clinical findings promoted a radical change in practice, through the use of the semirecumbent position in all mechanically ventilated patients. Here, we critically review the main indications, pulmonary effects, and controversies on the use of the semirecumbent position. Also, we will depict potential roles of prone and lateral positions in the prevention of ventilator-associated pneumonia. Our review will span from preclinical experimental insights to clinical evidence, and we will discuss potential controversies on the use of the semirecumbent position as the standard of care. We will also detail potential alternatives to ultimately improve outcomes of tracheally intubated and mechanically ventilated patients.
Keywords: ventilator-associated pneumonia; semirecumbent position; prone position; continuous lateral position; tracheal intubation; critical care